An effective back-off selection technique for reliable beacon reception in VANETs - Shah, Syed Adeel Ali; Ahmed, Ejaz; Qureshi, Muhammad Ahsan; Jan, Sadeeq; Noor, Rafidah Md (Wiley, 2019)
In safety-critical scenarios, reliable reception of beacons transmitted by a subject vehicle is critical to avoid vehicle collision. According to the employed contention window sizes in IEEE 802.11p, beacons are transmitted with a small contention window size. As a result, multiple vehicles contend for the shared channel access by selecting the same back-off slot. This is a perfect recipe for synchronous collisions wherein reliable beacon delivery cannot be guaranteed for any vehicle. We consider the problem of selecting the back-off slots from the current contention window to provide reliable delivery of beacons transmitted by a subject vehicle to its neighbors. Given a safety scenario, we propose a Pseudo-Random Number Generator (PRNG)-inspired back-off selection (PBS) technique. The proposed technique works on the hypothesis that synchronous collisions of beacons transmitted by a subject vehicle can be reduced if all its neighbors select different back-off slots (ie, not the back-off slot selected by the subject vehicle). The discrete-event simulations demonstrate that PBS can increase the overall message reception from a subject vehicle, in comparison with the uniform random probability back-off selection in IEEE 802.11p. © 2019 John Wiley & Sons, Ltd.